Makna Hidup Dibalik Seni Tradisional: Studi Fenomenologi Kebermaknaan Hidup Seniman Sunda - Rezza Pahruroji Priatama; Anwar Supenawinata; Ila Nurlaila Hidayat (Jurnal Psikologi Islam dan Budaya, 2019)
Globalization brings positive and negative impacts to the culture, including in Indonesia. One of the negative impacts is the decreasing interests of Indonesians on traditional arts, which may lead to less interests on career as an artist. However, artists in Sanggar Bandungmooi were different. The purpose of this study is to explore the meaning of life of local artists in Sanggar Bandungmooi. The method used is qualitative with phenomenology type. The data was collected using observation and interview. The subjects were two artists, aged 24 and 50 years old. The results show that both subjects have a meaning of life that is beneficial to others. Their meaning of life can help them to determine their life purposes. Both subjects find the meaning of life through their own efforts and the supports from the social environment. They try to anticipate negative consequences and show positive attitudes in facing life conditions.